Character analysis of the symbolic value of the Ngasa tradition - Anggara, Tio (Program Pascasarjana Universitas Negeri Yogyakarta, 2022)
The Ngasa traditional ceremony is one of the traditional ceremonies that still survives today. The Ngasa tradition is a tradition that aims to show gratitude for the abundance of blessings and graces given by God. This study aimed to determine the character values in the series of events and the tools used during the Ngasa tradition process. The approach used in this study is a qualitative approach with content analysis methods. Content analysis is used because the data to be studied are video documentation taken from several YouTube channels to explain the symbols of the Ngasa traditional ceremony in the Jalawastu area, Brebes Regency. The symbols in the tradition are interpreted to obtain the values contained in them. The character values studied in this study include the meaning of religion, togetherness, cooperation, hard work, simplicity, chastity, and sincerity.